DNA Barcoding of Six Commercially Important Groupers (Epinephelidae) from Langsa, Aceh, Indonesia - Fadli, Nur; Jumiati, Sri; Razi, Nanda Muhammad; Damora, Adrian; Muchlisin, Zainal A.; Dewiyanti, Irma; Ramadhaniaty, Mutia; Harnelly, Essy; Habib, Ahasan; Siti-Azizah, Mohd Nor (Bogor Agricultural University, Indonesia, 2024)
Groupers are among the fish groups that are difficult to recognize due to their high morphological similarities. Therefore, molecular techniques, particularly DNA barcoding, are extensively utilized to differentiate this fish group. This study aimed to analyze and validate six grouper species belonging to the Epinephelidae family that were harvested from Langsa district waters in Aceh province, Indonesia, based on DNA barcode data. It was conducted from June to December 2021, with the fish specimens collected from fishers at fish landing sites and the fish market in Langsa City, Aceh province. A total of 22 grouper sequences belonging to six species were generated, namely Epinephelus coioides, E. bleekeri, E. malabaricus, E. erythrurus, E. sexfasciatus and Mycteroperca poecilonotus (formerly Epinephelus poecilonotus). Genetic distance within these species ranged from 0.10 to 0.73% (average: 0.40%). Notably, E. malabaricus and E. coioides exhibited the closest genetic kinship (4.07%), while E. sexfasciatus and M. poecilonotus displayed the greatest genetic distance (19.33%). This study provides the first DNA reference for grouper in Langsa district, Indonesia, with significant implications for future sustainable grouper management.